Дослідження багатошарового поселення біля с. Буша - Косаківський, В.А.; Рудь, В.С. (Археологічні дослідження в Україні, 2010)
Over a period of three field seasons (2007—2009) the expedition of M. Kotsyubynskyi Vinnytsya State Pedagogical University conducted the research of the multilayer settlement in Busha village in Yampil Region of Vinnytsya Oblast. In 2009, excavations of the area of Trypillya culture previously studied in 2007 were ongoing; it was also prepared for conservation. The materials found here were related to the Middle Trypillya period (B I, В ІІ) and the Early Slavic times.